The Underdeveloped Areas Paradox: The Role of Infrastructure for Sustainable Community-Based Tourism - Emanuel de Rozari, Petrus; Timuneno, Tarsisius; Zebua, Darwin; Mariano Amleni, Rosarianto (Indonesian Association for Public Administration (IAPA), 2025)
This study investigates the implementation of Community-Based Tourism (CBT) in Ende Regency, Indonesia, a region characterized by the “Underdeveloped Regions Paradox,” where significant macroeconomic growth obscures severe micro-level poverty. The aim is to examine the degree to which fundamental components of Community-Based Tourism (CBT) enhance the sustainability of tourism, and, crucially, to explore the moderating effects of infrastructure and accessibility within this context. This study employs a qualitative case study methodology, integrating secondary data from government statistics and policy documents with primary insights gathered from field observations and extensive interviews performed in pivotal communities. The findings confirm that while community engagement, empowerment, and external aid are essential for the success of CBT, their effectiveness is fundamentally dependent on the existence of supportive infrastructure. Insufficient infrastructure presents a significant barrier, undermining community endeavors, whereas appropriate accessibility fosters positive outcomes. Additionally, the research highlights the critical impact of the quality of external support and the complex, dual-dimensional function of local cultural traditions. This paper’s importance comes from the fact that it provides a sophisticated developmental framework that sees foundational infrastructure not just as an extra piece, but as an essential part of building viable and sustainable CBT in underdeveloped areas. It also offers practical suggestions for integrated policy and practice.